2019
DOI: 10.1177/1350650119877775
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of non-asbestos friction lining material applied in automotive drum brake

Abstract: Automotive brakes are the important machine element which provides an artificial frictional resistance to control the speed of an automobile. In the present work, theoretical models for the coefficient of friction between brake drum and friction liner are generated and simulated using MATLAB Simulink. A test set up designed and manufactured according to the brake lining quality test procedure (SAE J661) is used to investigate tribological properties of a non-asbestos friction lining material having 11 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…However, the properties of FLM were taken from the literature. 26,[35][36][37] To replicate the exact braking operation of the drum brake, the constraints and loading conditions reported in Figure 4 were used in FEA. The brake drum was subjected to rotational velocity obtained from automobiles' speed.…”
Section: Modeling Of Automotive Drum Brake For Feamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the properties of FLM were taken from the literature. 26,[35][36][37] To replicate the exact braking operation of the drum brake, the constraints and loading conditions reported in Figure 4 were used in FEA. The brake drum was subjected to rotational velocity obtained from automobiles' speed.…”
Section: Modeling Of Automotive Drum Brake For Feamentioning
confidence: 99%
“…Kchaou et al 25 presented a comprehensive literature review on different testing and characterization methodologies for these materials. Shinde et al 26 reported a theoretical and experimental investigation of the FLMs under actual operating conditions. Manoharan et al 19 carried out an experimental study on the FLMs using a standard quality test procedure, SAE J661, exhaustively called a chase friction test.…”
Section: Introductionmentioning
confidence: 99%